Jurnalis Sebagai Dai di Media - Haris, Munawir (Tasamuh: Jurnal Studi Islam, 2020)
In the current reformation era marked by the rise of mass media as a means of mass communication and a means of forming public opinion, preachers, missionary activists, and Muslims. A journalist should be able to use the mass media to do da'wah as a worship field. A journalist who utilizes the mass media, especially printed media, carries out his da'wah that can be called a preacher 'who preaches bil qalam. This da'wah is called the da'wah bil qalam which basically conveys information about God, about nature and about the hereafter, and the value of eternity of life. Da'wah bil qalam is da'wah through printed media. Given the advances in information technology that enable a person to communicate intensely and cause the message of preaching to spread as widely as possible, preaching through writing, absolutely makes use of advances in information technology. This is where the role of Muslim Journalists takes place of a preacher who spreads goodness to humans.